2015
DOI: 10.1158/1541-7786.mcr-14-0344-t
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcome and EMT Suppression Mediated by a Lectin Domain Interaction of Endo180 and CD147

Abstract: Epithelial cell-cell contacts maintain normal glandular tissue homeostasis, and their breakage can trigger epithelialto-mesenchymal transition (EMT), a fundamental step in the development of metastatic cancer. Despite the ability of C-type lectin domains (CTLD) to modulate cell-cell adhesion, it is not known if they modulate epithelial adhesion in EMT and tumor progression. Here, the multi-CTLD mannose receptor, Endo180 (MRC2/uPARAP), was shown using the Kaplan-Meier analysis to be predictive of survival outco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 40 publications
8
32
0
Order By: Relevance
“…In line with our previous studies, where Endo180 has been shown to play a role in EMT and prostate cancer progression , and the spatiotemporal activation of actinomyosin‐based contractile signals and cell migration , we propose a model in which two functional CTLDs in Endo180, CTLD2 and CTLD4, are responsible for directly modulating PEC invasiveness (see supplementary material, Figure S6). We believe that the molecular basis of this regulation involves a switch between the closed and open conformation of Endo180's ectodomain .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In line with our previous studies, where Endo180 has been shown to play a role in EMT and prostate cancer progression , and the spatiotemporal activation of actinomyosin‐based contractile signals and cell migration , we propose a model in which two functional CTLDs in Endo180, CTLD2 and CTLD4, are responsible for directly modulating PEC invasiveness (see supplementary material, Figure S6). We believe that the molecular basis of this regulation involves a switch between the closed and open conformation of Endo180's ectodomain .…”
Section: Discussionsupporting
confidence: 86%
“…The mechanisms underpinning this phenomenon could involve activation of proteases that degrade the basal lamina or defective production and organization of its matrix components. The first mechanism is supported by the finding that Endo180 forms an EMT‐suppressor complex with the extracellular matrix metalloproteinase inducer CD147 , and its targeted blockade results in down‐regulation of MT1‐MMP and uPA (see supplementary material, Figure S5), which both drive basal lamina matrix degradation . The latter mechanism is supported from the finding in a different cellular context, whereby Endo180 orchestrates collagen deposition by primary human osteoblasts .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Most researches on MRC2 to date have focused on its role in the development of cancer, as it can promote breast tumor growth, 17 co-operate with the matrix metalloproteinase to remodel of extracellular matrix that attenuate renal fibrosis, 28 and predict prognosis of hepatocellular carcinoma 18 and prostate cancer. 29 Besides, MRC2 is also closely related to collagen turnover. 30 In our study, we found that both estrogen and 1-MT promoted the expression of MRC2 in ESCs, which indicates that MRC2 is downstream to estrogen and IDO1.…”
Section: Discussionmentioning
confidence: 99%
“…These acini also have the characteristics of highly organized PECs with apical-to-basal polarity and a visible luminal space 13,20 .…”
Section: Prostate Acini Cultured On Stiff Rbmmentioning
confidence: 99%